X-ray emission of the radio-loud quasar SDSS J121426.52+140258.9: independent variations between optical/UV and X-ray emission. Issue 1 (22nd December 2022) - Zhou, Minhua; Gu, Minfeng; Liao, Mai; Anjum, Muhammad S
ABSTRACT: To understand the X-ray emission of active galactic nuclei (AGNs), we explored the optical-to-X-ray variation correlation of a radio-loud quasar (RLQ) SDSS J121426.52+140258.9 (hereafter J1214+1402) with multi-epoch observations by the Swift and XMM–Newton telescopes. With the historical multiband data, we found that the infrared-to-X-ray flux of RLQ J1214+1402 should not be dominated by the beamed-jet emission. The Swift optical/UV and X-ray light curves showed that J1214+1402 has two optical states, with low flux before 2014 April 8 and high flux after 2014 June 11, but has no significant X-ray variations during the time range between 2007 March 9 and 2014 August 4. This result was supported by the XMM–Newton observations in the time overlapping with Swift . Interestingly, the early XMM–Newton data prior to the Swift time present two unusual emission epochs when J1214+1402 has relatively low optical fluxes but has the brightest X-ray fluxes. The overall independence of optical-to-X-ray variation seems hard to describe by the disc–corona model. With the X-ray spectral fitting, we find that the soft X-ray excess in J1214+1402 appears only during the high optical state when the X-ray emission is at a low state. The soft X-ray excess in J1214+1402 is difficult to explain by an ionized accretion disc; instead, it may be related to the warm corona.